Penerapan Model Pembelajaran Kooperatif Tipe Student Teams Achievement Divisions (STAD) untuk Meningkatkan Hasil Belajar Materi Daur Hidup Hewan di Kelas IV MIS NW Dasan Tapen - Faruk, Ambar (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2025)
Learning success is highly influenced by the teacher’s role in mastering the subject matter and applying an appropriate instructional model, one of which is the cooperative learning model of the Student Teams Achievement Divisions (STAD) type, which is believed to enhance student motivation and enthusiasm for learning. This study aims to examine the implementation of the STAD cooperative learning model and to identify its supporting and inhibiting factors in improving the learning outcomes of fourth-grade students on the topic of animal life cycles at MIS NW Dasan Tapen. A descriptive qualitative approach was used, with data collected through observation, tests, interviews, field notes, and documentation. The results indicate that the implementation of the STAD model improved student learning outcomes, as reflected in the increase in the percentage of learning mastery from 65% in the pretest to 100% in the posttest. Additionally, the learning process showed improved student participation and comprehension of the material taught. These findings indicate that the STAD learning model is effective not only in improving cognitive achievement but also in fostering active student engagement during the learning process. The practical implication of this study underscores the importance of selecting appropriate instructional models to optimally achieve learning objectives.